Antecedents of impulse buying and their implications for online customer satisfaction - Putri Zhafira Chairunnisa; Heni Rahayu Rahmawati (Faculty of Economics and Business Mulawarman University, 2023)
Customer satisfaction is the target of every marketing effort, low e-commerce conversion rates are certainly influenced by customer satisfaction after making a transaction. Impulse buying is a crucial factor in a consumer's shopping experience. This study aims to determine the relationship between electronic word of mouth, perceived ease of use, and website quality on impulse buying as the intervening and customer satisfaction on the Sociolla website. The research was conducted using a quantitative method with PLS-SEM analysis using SmartPLS 3. With a total sample of 105 people in Samarinda. The results showed that eWOM has a positive and significant effect on impulse buying and customer satisfaction, perceived ease of use has a positive and insignificant effect on impulse buying but has a significant effect on customer satisfaction, website quality has a positive and insignificant effect on impulse buying but has a significant effect on customer satisfaction.